New standards in the treatment of an old pathology: miogenic torticolis - Huerta-Mezones, Manuel F. (2018)
Introduction: The diagnosis and timely treatment of congenital muscular torticollis with physiotherapy can avoid their sequence of craniofacial asymmetry, which is difficult to correct once they have been established1. Cases that do not respond to initial medical treatment benefit from surgery. Objectives: To identify the clinical and surgical characteristics of the pediatric population with surgical treatment for congenital torticollis. Methods: Descriptive and retrospective study, carried out in the Pediatric Unit of the Head and Maxillofacial Surgery Service of the Edgardo Rebagliati Martins National Hospital. The sample consisted of 30 pediatric patients, with surgical treatment for congenital muscular torticollis during the last 15 years, who fulfilled the inclusion and exclusion criteria, the patients' clinical histories were reviewed. The statistics used were descriptive. Results: The age range of patients  was from 2 months to 10 years of age, the  sex predominated was male , the most affected side was the right side, the surgical treatment consisted of myotomies of sternocleidomastoid muscle insertions through direct approach by small transverse incisions, the correction amount had no correlation with age or with the severity of the deformity, good results were obtained even in severe deformities. Conclusion: In all cases we achieved substantial improvement, without complications and with acceptable scars; The lateral column of the neck at the site of the sectioned muscle recovered its continuity, without perception of abrupt cut, depression or subsidence. We did not observe a correlation between the improvement achieved and the severity of the deformity, nor with the age of the patient at the time of surgery. Key words: Congenital torticollis; Myogenic torticollis; Myotomy. (source: MeSH NLM)   DOI: 10.25176/RFMH.v18.n2.1281